Subcritical Water Processing of Grape Pomace (Vitis vinifera L.): Kinetic Evaluation of Sugar Production and By-Product Formation - Luiz Eduardo Nochi Castro; William Gustavo Sganzerla; Larissa Resende Matheus; Vanessa Cosme Ferreira; Mauricio Ariel Rostagno; Tania Forster-Carneiro (Biomass, 2025)
This study investigates the competitive dynamics of reducing sugar production and degradation during the subcritical water processing (SWP) of lyophilized grape pomace (LGP), with the goal of optimizing sugar yield. Under the SWP conditions tested (150 °C, 150 bar, pH 7, S/F of 30 g water g−1 LGP, and a flow rate of 5 mL min−1), we achieved a reducing sugar yield of 296.0 mg sugars g−1 LGP, effectively balancing sugar production and degradation. Sugar yield decreased as the temperature increased from 150 °C to 210 °C, due to the degradation of monosaccharides into by-products like furfural and 5-HMF. A first-order reaction model was developed to better understand the kinetic competition between sugar formation and degradation at varying temperatures. The highest sugar yield occurred at 150 °C, where sugar production was maximized, and degradation was minimized. These findings offer valuable insights for subcritical water processing in the valorization of LGP into fermentable sugars while minimizing the formation of undesirable by-products.